Memorial The General Jewish Workers` Union in Poland to the Polish government of Prime Minister General Wladyslaw Sikorski in France = Memoriał Ogólnego Żydowskiego Związku Robotniczego w Polsce do rządu premiera generała Władysława Sikorskiego we Francji - Miszewski, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The General Jewish Workers Bund of Poland sent memorandum on the position of Jews in occupied Poland in April 1940 to The Polish Government in France. In sent document Bund mentioned discrimination of Jews in the Second Polish Republic and fact there was plan of support of Jewish emigration to Palestine. It declared active struggle for an independent Poland with the German and Soviet occupiers.
Keywords: Jewish minority in Poland; Polish Jews; the Bund; the German extermination of the Jews; mniejszość żydowska w Polsce; polscy Żydzi; Bund; niemiecka eksterminacja Żydów